(3OjhGf GdeJdeSs - (3GdeJdeS , LQjQ Hf YHO GdeSjM Hf RjO GdCMeSj GdVHYj , J fMh (B50 (3b g` s ((3GdMGL YHOGddg Gdecj s)
(3ChdgG (B:s
(3QhGjI CHj GdMSf GdCKQe, bGd CHhYHjOI(B: (3cGf SHH gLGA GdeJdeS, hGSeg LQjQ GHf YHOGdYRi Yf fSH GdeJdeS abGd(B: (3jRYe Cfg ef Hfj VHjYI s
(3BNQgG (B:s
(3hEfj dCLeYgG hCYWj QbGHgG hCefYgG hGdNjd jYKQ HGdOe fLR TYQ GdeJdeS hGdMeO ddg hMOg, hUdi Gddg Ydi fHjg eMeO hBdg hYJQJg GdWGgQjf s
(3GfXQ GdLRA GdChd HQbe (B357 (3COHs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B119 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B129s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B191 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B809s
Keywords: (3GdCOHs